Emerging role of exosomes in vascular diseases - Ren, Yi; Zhang, Honggang (Frontiers in Cardiovascular Medicine, 2023)
Exosomes are biological small spherical lipid bilayer vesicles secreted by most cells in the body. Their contents include nucleic acids, proteins, and lipids. Exosomes can transfer material molecules between cells and consequently have a variety of biological functions, participating in disease development while exhibiting potential value as biomarkers and therapeutics. Growing evidence suggests that exosomes are vital mediators of vascular remodeling. Endothelial cells (ECs), vascular smooth muscle cells (VSMCs), inflammatory cells, and adventitial fibroblasts (AFs) can communicate through exosomes; such communication is associated with inflammatory responses, cell migration and proliferation, and cell metabolism, leading to changes in vascular function and structure. Essential hypertension (EH), atherosclerosis (AS), and pulmonary arterial hypertension (PAH) are the most common vascular diseases and are associated with significant vascular remodeling. This paper reviews the latest research progress on the involvement of exosomes in vascular remodeling through intercellular information exchange and provides new ideas for understanding related diseases.